Pemberian Virgin Coconut Oil (VCO) Untuk Menurunkan Gangguan Integritas Kulit - Saniyyah Elfadl; Putri Eka Sudiarti; Gusman Virgo (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Skin integrity disorders are conditionsin which individuals are at risk of damage to the epidermis and dermislayers of the skin. These skin integrity disordersinclude rough, dry, itchy skin with a blackish color andsmall crackson the skin. If left untreated, this will cause the skin tobecome inflamed or even infected.An. N's complaints include dry, rough, itchy, scaly skin with a darkened appearance sincehe began undergoing regular blood transfusions due to his thalassemia condition.This study used direct observation methods to assess,analyze data, and diagnose patients with dry skin with one respondent, An.. It was conducted in the Thalassemia room of Arifin Achmad Regional General Hospital in Riau Province. The purpose of this scientific workis to obtain an overview ofskin integrity with the application of virgin coconut oil. The results of this nursing care showed a decrease in skin integrity disorders from a scale of 3to a scale of 0 after 3 days of treatment. This indicates that the application of virgincoconut oil can reduce skin integrity disorders in children. It is hoped that patients and their families willapply Virgin Coconut Oil to dry skin to obtain better results so that the skin returns to normal.